Homozygosity in the APOE 3 Polymorphism Is Associated With Less Depression and Higher Serum Low-Density Lipoprotein in Chinese Elderly Schizophrenics - Li, Wei; Ban, Chunxia; Yue, Ling; Sun, Lin; Li, Xia; Xiao, Shifu (Frontiers in Endocrinology, 2020)
Abstract Background Depressive symptoms are common comorbidities in schizophrenia. However, the effect of APOE E3 on depressive symptoms has never been investigated in Chinese aging with schizophrenia. Objective This cross-sectional study was to investigate the effect of APOE E3 on blood lipid metabolism and depressive symptoms in Chinese elderly schizophrenics. Method: 301 elderly schizophrenics (161 males, age ranges from 60 to 92 years, with an average age of 67.31±6.667) were included in the study. Depressive symptoms were assessed using the Geriatric Depression Scale (GDS). And APOE gene polymorphism was determined by polymerase chain reaction (PCR). Correlations of GDS and serum low density lipoprotein (LDL) with APOE genotypes were assessed. Results The concentration of LDL in APOE E3 group was significantly higher than that in without APOE group, while the scores of GDS of APOE E3 group were lower than that in without APOE E3 group. By using partial correlation analysis and controlling age, gender, duration of disease and hyperlipidemia, we found that the scores of GDS were significantly correlated with LDL (r=-0.194, p= 0.016). Conclusions APOE E3 is associated with less depressive symptoms and higher serum LDL in Chinese elderly patients with schizophrenia, and there is a negative correlation between depressive symptoms and LDL.